Reliability of radiographic measures in infants with clubfoot treated with the Ponseti method. (April 2015) - Zimmerman, Catherine C.; Nemeth, Blaise A.; Noonan, Kenneth J.; Vanderbilt, Timothy P.; Winston, Mark J.; O'Halloran, Conor P.; Sund, Sarah A.; Hetzel, Scott J.; Halanski, Matthew A.
Purpose: The aim of this study was two-fold: (1) to determine if radiographic measures can be reliably made in infants being treated with the Ponseti method and (2) to document radiographic changes before and after Achilles tenotomy. Methods: A retrospective radiographic and chart review was performed on children with clubfoot treated by the Ponseti method at a single institution over a 10-year period. Five independent reviewers measured a series of angles from a lateral forced dorsiflexion radiograph taken prior to and following Achilles tenotomy. These measures were taken in triplicate to determine the intra- and inter-reader reliability of dorsiflexion, tibio-calcaneal, talo-calcaneal, and talo-first metatarsal angles. Results: Thirty-six subjects (56 feet) were treated with the Ponseti method and met the inclusion criteria. The median (range) age of patients at the time of tenotomy was 52 (34–147) days. The intra-reader reliability [intra-rater correlation coefficient (ICC)] for each of the measured angles pre- and post-tenotomy ranged from 0.933 to 0.995 and 0.864 to 0.995, respectively. Similarly, the inter-reader reliabilities (ICC) ranged from 0.727 for the pre-tenotomy (talo-calcaneal) to 0.950 for the post-tenotomy (talo-first metatarsal) angles. The mean differences between pre- and post-tenotomy radiographs were: dorsiflexion increase of 17°, tibio-calcaneal angle increase of 19°, talo-calcaneal angle increase of 9°, and talo-first metatarsal angle increase of 10° ( p -value ≤0.001 for all measurements except the talo-first metatarsal angle, with a p -value of 0.001). Conclusions: Reliable radiographic measures can be made from lateral dorsiflexion radiographs of clubfeet treated with the Ponseti method before and after Achilles tenotomy.